Introduction to the Special Issue: New and Interdisciplinary Approaches to Linguistic Relativity. Issue 3 (September 2016) - Athanasopoulos, Panos; Bylund, Emanuel; Casasanto, Daniel
Abstract : This Special Issue of Language Learning presents an interdisciplinary state‐of‐the‐art overview of current approaches to linguistic relativity. It contains empirical and theoretical studies and reflections on linguistic relativity from a variety of perspectives, such as associative learning, conceptual transfer, multilingual awareness, perceptual learning, semantic priming, and neurophysiology. This introduction presents the context and rationale of the Special Issue.